コラーゲン含有エモリエントクリームの角化異常症，湿しん・皮膚炎，特に小児乾燥性湿しんに対する有効性について - TEZUKA Tadashi; KURIMOTO Takehisa (Skin research, 1982)
In recent years, the emollient creams whichcontain urea, were used to the treatment ofichthyosis and senile xerotic skin conditions, andremarkable improvement was observed. However, these creams could not use on the facenor the dry skin condition of atopic dermatitisbecause of infrequent, trancient irritation.A emollient cream which contains the solublecollagen, oil in water in emulsion, was used tothe treatment of several xerotic skin conditions, especially the dry skin and a fine, skin coloredpapular eruptions seen in atopic dermatitis (19cases of atopic dermatitis, 7 of senile xeroticskin conditions, 3 of ichthyosis vulgaris and oneof acquired ichthyosis). The effectiveness inatopic dermatitis was 84% and, 71% in senilexerosis and 100% in ichthyosis. No side effectwas seen at all. This emollient cream was foundto be remarkably effective for the treatment ofthe dry skin and a fine, papular eruptions ofatopic dermatitis. 小児乾燥性湿疹9例, アトピー性皮膚炎6例, 乳児湿疹4例の有効以上の有効率は84%で, 老人性乾皮症5例, 冬期湿疹1例, 乾皮症1例では有効以上の有効率は71%, 魚鱗癬群 (尋常性魚鱗癬3例, 続発性魚鱗癬1例) では全例が有効以上であった。また, 従来の外用剤と異なりこのクリームの使用感は良く患者の長期ケアーに良好と考えられる。